Permainan Flashcard Fun Time untuk Mengenalkan Kosakata Bahasa Inggris pada Anak Usia Dini - Laela, Nur; Imani Khan, Rosa; Kurnia Wati, Epritha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study develops the Flashcard Fun Time game to introduce English vocabulary to early childhood. The approach uses Research and Development (R&D) with three stages: information gathering through literature review, design planning, and preliminary product development with feasibility evaluation. Validation was conducted by three material and three game experts using a 1–5 Likert Scale questionnaire, analyzed with Aiken's V index. Results showed all aspects had Aiken's V ≥ 0.5 with averages of 0.84 (material) and 0.83 (game experts), indicating Flashcard Fun Time is valid and feasible. The product combines hand-shaped flashcards, interactive PowerPoint, and digital spinner for multimodal (visual, auditory, kinesthetic) enjoyable learning. Conclusion: Flashcard Fun Time is an effective innovative media for introducing English vocabulary to early childhood.